Addition of yellow strawberry guava leaf extract in the diet of laying hens had antimicrobial and antioxidant effect capable of improving egg quality. (October 2020) - dos Santos, Ariane F.A.; Da Silva, Aleksandro S.; Galli, Gabriela M.; Paglia, Eduarda B.; Dacoreggio, Marina V.; Kempka, Aniela P.; Souza, Carine F.; Baldissera, Matheus D.; da Rosa, Gilneia; Boiago, Marcel M.; Paiano, Diovani
Abstract: The aim of this study was to determine the effects of the inclusion of yellow strawberry guava leaf extract (SGLE) as an additive in laying diets on productive performance, immunity, metabolism, and antioxidant response of semi-heavy laying hens (Isa Brown), as well its effects on egg quality. Five treatments with different SGLE levels (0.0, 0.05, 0.10, 0.15, and 0.20/kg feed), five repetitions per treatment, and three birds per repetition were used. The addition of increasing levels of SGLE linearly reduced total bacterial count (TBC) in feces. The number of total leukocytes was lower in the blood of chickens that consumed SGLE due to the lower number of heterophiles, eosinophils and lymphocytes. The inclusion of SGLE in the diet stimulated the activity of glutathione S-transferase and reduced serum lipid peroxidation (LPO) levels. A linear effect in the fresh eggs of the chickens that consumed SGLE was observed, that is, we recorded lower TBC and Escherichia coli counts in the shells, as well as greater total antioxidant capacity (ACAP) in the yolk. In eggs stored for four weeks, we founder lower albumen pH and lower LPO of yolks when the birds consumed SGLE, associated with greater specific gravity of the egg and ACAP levels of the yolks. The conclusion of this study was that the inclusion of SGLE produced better quality eggs, characterized by internal oxidative stability and less bacterial contamination in the shell, both of which desirable effects from the standpoint of the consumer.